Ganap na babae a framing analysis on the portrayal of transgender narratives in Kapuso Mo, Jessica Soho episodes (2014-2024) - Serrano, Harry B.
The narratives surrounding transgender persons in the Philippine media are often marred by sensationalism. The media tends to feature odd stories and brutal depictions of the community, which is frequently plagued by misgendering, deadnaming, and the reinforcement of the gender binary. The study focused on examining Kapuso Mo, Jessica Soho’s (KMJS) reporting practices, specifically when surfacing transgender narratives. Guided by de Vreese’s integrated process of framing model, the study enforced a three-part framing analysis from the production level, the frames in the episodes, and the framing effects on the transgender community. It was found that the ethical standards the KMJS production abides by were more intuitive than prescriptive. The producers did not strictly follow specific gender-sensitive guidelines when telling the stories of transgender persons. Over the years, the theme of equal rights has become increasingly prominent, while the theme of abnormality has declined, however, it has not disappeared entirely. The episodes still contained delegitimizing language, often suggesting that transgender women are not “real” women. Moreover, the transgender community highlighted several recommendations for the magazine show, which included consultations with trans advocacy groups, shying away from spectacularized narratives, and highlighting institutional gaps that contribute to the community’s struggles.